Uncertain Futures: Organisational Influences on the Transition from Work to Retirement. Issue 3 (22nd June 2018) - Phillipson, Chris; Shepherd, Sue; Robinson, Mark; Vickerstaff, Sarah
Abstract : The promotion of extended working life has created a period of uncertainty between the ending of work and the beginning of retirement. This period of the life course is now 'open-ended' in respect of whether older workers decide to remain in employment or leave working. However, the choices available are framed within public policy and organisational contexts as well as personal circumstances. The study reviews the organisation of 'work-ending', the construction of age within organisations, and the influences on provision of support in late working life. The article concludes with a discussion on the range of pressures that might limit control over pathways through middle and late working careers.